2019
DOI: 10.1016/j.jse.2018.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty for acute fractures in the elderly: is it worth reattaching the tuberosities?

Abstract: Hypothesis: Reverse Shoulder Arthroplasty (RSA) may be indicated in displaced proximal humerus fractures in elderly patients. We hypothesized that tuberosity fixation and healing around the prosthesis would result in better outcomes and patient satisfaction. Methods: Thirty-eight acute displaced or dislocated 3-and 4-part fractures in elderly patients were treated with reattachment of the tuberosities around a RSA. The mean age at surgery was 80 ± 4 years (range, 70-88 years). A specific reverse fracture stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
111
2
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 31 publications
12
111
2
14
Order By: Relevance
“…Our data supports those findings of Grubhofer et al [ 39 ] and Boileau et al [ 40 ] that patients with GT healing improve in external rotation, forward flexion, and subjective function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data supports those findings of Grubhofer et al [ 39 ] and Boileau et al [ 40 ] that patients with GT healing improve in external rotation, forward flexion, and subjective function.…”
Section: Discussionsupporting
confidence: 93%
“…This higher rate of anatomical tuberosity healing in group B could account for the better results on average in CS, ROM, and SSV because according to theoretical models, GT healing does improve stability through deltoid wrapping [ 41 ]. Tuberosity healing has been described in the literature with similar GT healing of 65–84% [ 21 , 39 , 40 , 42 , 43 ] comparable to a rate of 82% for both group A and B.…”
Section: Discussionmentioning
confidence: 66%
“…We observed that increased patient mobility corresponded to CS improvement (79 versus 55). Boileau et al 28 summarize their study by stating that tuberosity healing not only improves FE and ER, but also the patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is in line with more recent studies, 22,29,30 and it is superior to older works. Boileau et al 28 describe a higher healing rate, of 84%, arguing that tuberosity healing in fractures submitted to RSP is a reproducible procedure even in the elderly. In addition, new developed prostheses, designed specifically for fractures and presenting a window in the metaphyseal region, enable better tuberosity integration and healing.…”
Section: Discussionmentioning
confidence: 99%
“…Ob die Tuberkula refixiert oder reseziert werden sollen, wird unterschiedlich beurteilt. Dabei wird über bessere Ergebnisse in der aktiven Außenrotation nach Refixation und Einheilung der Tuberkula in nahezu anatomischer Position am proximalen Schaft berichtet [2][3][4]. Auch die Häufigkeit von Luxationen wird bei refixierten Tuberkula reduziert [5].…”
Section: Hintergrundunclassified